Role of the Excitability Brake Potassium Current Ikd in Cold Allodynia Induced by Chronic Peripheral Nerve Injury - Ugarte-Martinez, G; Madrid-Montecinos, R; Gonzalez-Figueroa, A; Pertusa-Pastor, M; Piña-Muñoz, R (Society for Neuroscience, 2017)
Cold allodynia is a common symptom of neuropathic and inflammatory pain following peripheral nerve injury. The mechanisms under-lying this disabling sensory alteration are not entirely understood. In primary somatosensory neurons, cold sensitivity is mainly deter-mined by a functional counterbalance between cold-activated TRPM8 channels and Shaker-like Kv1.1-1.2 channels underlying the excitability brake current IKD. Here we studied the role of IKD in damage-triggered painful hypersensitivity to innocuous cold. We found that cold allodynia induced by chronic constriction injury (CCI) of the sciatic nerve in mice, was related to both an increase in the proportion of cold-sensitive neurons (CSNs) in DRGs contributing to the sciatic nerve, and a decrease in their cold temperature threshold. IKD density was reduced in high-threshold CSNs from CCI mice compared with sham animals, with no differences in cold-induced TRPM8-dependent current density. The electrophysiological properties and neurochemical profile of CSNs revealed an increase of nociceptive-like phenotype among neurons from CCI animals compared with sham mice. These results were validated using a mathe-matical model of CSNs, including IKD and TRPM8, showing that a reduction in IKD current density shifts the thermal threshold to higher temperatures and that the reduction of this current induces cold sensitivity in former cold-insensitive neurons expressing low levels of TRPM8-like current. Together, our results suggest that cold allodynia is largely due to a functional downregulation of IKD in both high-threshold CSNs and in a subpopulation of polymodal nociceptors expressing TRPM8, providing a general molecular and neural mechanism for this sensory alteration. © 2017 the authors.